Development Of Crash Resistance Car Bumpers Based On Bio-Composites And Hybrids - Pang, Chin Wee (Universiti Sains Malaysia, 2017)
Generally, composite material is a material made from two or more constituent materials of different properties. Composite materials are highly utilized in the current era due to their tailored specified properties, such as high strength-to-weight, corrosion resistance, inflammable properties, wear resistance and etc. In this study, mechanical properties of bio composite materials, such as coir, and palm oil fibre, are to be analysed and evaluated thoroughly. Fabrication methods, such as compression moulding and resin film infusion method were used to manufacture the specimens for the test and analysis. Impact test, tensile test, and compression test were carried out simultaneously during analysis and evaluation process. The results from tensile, compression and impact testing were tabulated and plotted into graphs for analysis. Bar charts which include specific mechanical properties were plotted to compare the properties of the composites (GFRC, HPRC, HCRC, PFRC, CFRC). Moreover, hybridization of natural fibre has shown significant increase in tensile and impact testing, whereas for compression testing, no significant change was identified. Eventually, a crash resistance car bumper will be developed based on these bio composite and hybrids. ABSTRAK Secara umumnya, bahan komposit adalah bahan yang terdiri daripada dua atau lebih bahan konstituen dengan sifat yang berbeza. Bahan komposit kerap digunakan dalam era semasa kerana memiliki sifat-sifat yang amat berguna, seperti rasio kekuatan-berat yang tinggi, rintangan kakisan, sifat mudah terbakar, tahan lasak dan lain-lain. Dalam kajian ini, sifat-sifat mekanikal yang dimiliki oleh bahan komposit bio, seperti sabut , dan serat kelapa sawit, telah dianalisis dan dinilai dengan teliti. Kaedah fabrikasi, seperti acuan mampatan dan kaedah pemindahan resin telah digunakan untuk menghasilkan spesimen untuk ujian dan analisis. Ujian impak, ujian tegangan dan ujian mampatan telah dijalankan semasa analisis dan penilaian proses. Keputusan daripada tegangan, mampatan dan impak telah dikaji dan diplot sebagai graf untuk analisis. Carta bar yang mengandungi sifat-sifat spesifik mekanikal telah diplotkan untuk dibandingkan antara GFRC, HPRC, HCRC, PFRC, CFRC. Selain itu, hibridisasi serat semula jadi telah menunjukkan peningkatan yang ketara dalam ujian tegangan dan impak, manakala bagi ujian mampatan, tiada perubahan ketara telah dikenalpasti. Akhirnya, bumper kereta telah dihasilkan berdasarkan kepada komposit bio and komposit hibrid.